CRAM-A indicates IFN-γ-associated inflammatory response in breast cancer. Issue 2 (December 2015) - Sarmadi, Parisa; Tunali, Gurcan; Esendagli-Yilmaz, Guldal; Yilmaz, Kerim Bora; Esendagli, Gunes
Highlights: The atypical chemokine receptor CCRL2 is constitutively expressed in breast cancer. CCRL2 expression is specific to malignant epithelium and inflammatory status. The rare isoform of CCRL2, CRAM-A is specifically upregulated upon IFN-γ exposure. CRAM-A marks inflammation and may serve as an immune modulator in breast cancer. Abstract: Atypical chemokine receptors (ACKRs) function as endpoint regulators of chemokine gradients. These non-signaling receptors that are transiently expressed under inflammatory conditions have critical roles in the control or maintenance of immune responses. Alternatively, here, CCRL2 (ACKR5) expression was determined to be constitutive in breast cancer cells. Increased amount of CCRL2 was also found in breast tumor tissues with high immune infiltration. Its expression was upregulated in the presence of pro-inflammatory cytokines, IL-1β, TNF-α, IL-6, and especially IFN-γ⋅ Moreover, an alternative transcript of CCRL2 gene, CRAM-A, was specifically expressed in a transient fashion under the influence of IFN-γ. CRAM-A expression was also positively correlated with the presence of IFN-γ mRNA in patient samples. CCRL2-associated chemotactic molecules, chemerin, CCL19 and CCL5, were also detected in cancer tissues and CCL5 mRNA level was correlated with that of CRAM-A and IFN-γ. Hence, in breast cancer, CRAM-A becomes specifically upregulated under inflammatory stimuli and may serve as a potential marker of immune response.